Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.28991/cej-2021-03091753
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Carbon Fiber Filament Reinforcing Cement Mortar

Abstract: This paper aims to study the effect of Carbon Fiber Filament (CFF) with different ratios and lengths on the physical and mechanical properties of cement mortar. An experimental program included 3 cm fixed length of CFF with 0, 0.25, 0.5, 0.75, and 1% different ratios by weight of cement addition were used in cement mortar cubes. Another experimental program of 0.5% CFF ratio with 1, 2, 3, 4, and 5 cm different lengths by weight of cement addition was used in cement mortar prisms. The physical and mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The hardened density of all three specimens increased with time as shown in Figure 5, which is consistent with the previous literature [1,2,11,[21][22][23]. Furthermore, hardened density of the cement paste is influenced by length of curing period [24].…”
Section: Hardened Density Of Cement-pastesupporting
confidence: 90%
See 1 more Smart Citation

Engineering Properties of Cement-Paste with Polypropylene and Carbon Fibres

Anand Ryan Thurairajah,
Ahmad Nurfaidhi Rizalman,
Eliezer Nevall Anthony
et al. 2024
ARAM
“…The hardened density of all three specimens increased with time as shown in Figure 5, which is consistent with the previous literature [1,2,11,[21][22][23]. Furthermore, hardened density of the cement paste is influenced by length of curing period [24].…”
Section: Hardened Density Of Cement-pastesupporting
confidence: 90%
“…According to Paul et al, [9], the strength improvement in concrete was because the fibre acted as a bridge material that keep the concrete particles near to another. However, the addition of fibres reduced the slump of the concrete [10][11][12][13]. This was because the flow of fresh concrete was restricted by the presence of carbon fibre [14].…”
Section: Introductionmentioning
confidence: 99%

Engineering Properties of Cement-Paste with Polypropylene and Carbon Fibres

Anand Ryan Thurairajah,
Ahmad Nurfaidhi Rizalman,
Eliezer Nevall Anthony
et al. 2024
ARAM
“…This outcome occurred due to the fresh concrete movement obstruction from the fibre interaction with other concrete constituents [9]. Previous studies also demonstrated a positive correlation between the higher fibre percentage and fibre length in improving the compressive and flexural strength of concrete [6][7][8][9][10][11][12]. These improved concentre properties were attributed to the fibres, serving as a bridge to maintain the proximity of concrete particles [13].…”
Section: Introductionmentioning
confidence: 96%
“…Numerous studies demonstrated that gradually adding carbon fibre into concrete reduced workability [5][6][7][8]. This outcome occurred due to the fresh concrete movement obstruction from the fibre interaction with other concrete constituents [9].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of fiber reinforcement and/or nanoparticles into cement composites is a common modification method, but fiber and ordinary nanomaterials cannot control the microstructure of the cement hydration products, and it is difficult to block harmful substances from penetration and to protect the reinforcement from corrosion. As a result, reinforcement corrosion may occur [ 10 , 11 , 12 ]. Permeability is one of the most important indexes of the durability of cement-based materials.…”
Section: Introductionmentioning
confidence: 99%